Can mass media interventions reduce child mortality?. Issue 9988 (4th July 2015) - Head, Roy; Murray, Joanna; Sarrassat, Sophie; Snell, Will; Meda, Nicolas; Ouedraogo, Moctar; Deboise, Laurent; Cousens, Simon
Summary: Many people recognise that mass media is important in promoting public health but there have been few attempts to measure how important. An ongoing trial in Burkina Faso (ClinicalTrials.gov, NCT01517230 ) is an attempt to bring together the very different worlds of mass media and epidemiology: to measure rigorously, using a cluster-randomised design, how many lives mass media can save in a low-income country, and at what cost. Application of the Lives Saved Tool predicts that saturation-based media campaigns could reduce child mortality by 10–20%, at a cost per disability-adjusted life-year that is as low as any existing health intervention. In this Viewpoint we explain the scientific reasoning behind the trial, while stressing the importance of the media methodology used.